TECHNOLOGY-MEDIATED COMMUNICATIONS NETWORK IN THE MULTIMEDIA JOURNALISM - Roswita Oktavianti; H. H. Daniel Tamburian (Mediakom, 2020)
The proliferation of technology led to a growing number of groups who interact through a mediated channel. A group of people creates a social network that consists of a workflow network, a communications network, and a friendship network. It referred to the existence of either a professional or a friendship network. As an individual who tends to gather as a group, journalists using a set of communication technology to connect to those who have the same interest and give a benefit to them. This study will identify the technology-mediated communication networks followed by journalists, that is, workflow networks, communication networks, and friendship networks. Then, how the attribute of networks, and how journalists still exist as well as leaves in those networks. In this study, a technology-mediated communication network refers to WhatsApp instant messaging groups. The researcher using a case study as a research strategy that has focused on online and print journalists. The researcher did this research during Pandemic Covid-19, so it affected data gathering. The data collecting technique has done by face-to-face interviews with journalists at a different time and by imposing health protocol. The result of this study shows that multimedia journalists enrolled in workflow networks and friendship networks that consist of the employee under one media company. These networks are more stabilized and long-lasting. Also, journalists become a member of communication networks which are consist of journalists from different media companies, public relations officer, or the executive of its company. These networks are more temporary. The more multimedia journalist workload, the higher the need for communication networks. Journalists will decide to join, to leave, or still exist in a network if the administrator can maintain the dynamic of its network. In other words, a network administrator should choose a member selectively, treat all members fairly, pay attention to qualities and quantities of information shared, and lastly to ensure that the network gives benefits to journalists. The proliferation of technology is led to a growing number of groups who interact through a mediated channel. A group of people creates a social network that consists of a workflow network, a technology-mediated communications network, and a friendship network. It referred to the existence of either a professional or a friendship network. As an individual who tends to gather as a group, journalists using a set of communication technology to connect to those who has the same interest and give a benefit to them. This study will identify what kind of networks followed by journalists, what are technologies used by journalists in a technology-mediated communication network, how journalists enroll as a member in the network and the reasons why journalists still exist as well as leave a network. The researcher using a case study as a research strategy that has focused on online and print journalists. All of the journalists are a member of WhatsApp instant messaging groups. The researcher did this research during Pandemic Covid-19 so it would affects data gathering. The data collecting technique is done by face-to-face interviews with journalists at a different time and by imposed health protocol. The result of this study shows that multimedia journalists become a member of a network because the information and news material shared in it. The member of a network are journalists from different media, sometimes there are public relations staff or company executives. Journalists will decide to join, to leave, or still exist in a network if the administrator can maintain a dynamic of a network. In other words, a network administrator should choose a member selectively, treat all members fairly, pay attention to quality and quantity of information shared, and lastly to ensure that the network gives benefits to journalists.